Antioxidant activities of different parts of Musa sapientum L. ssp. sylvestris fruit - Mohammad Zafar Imam, Saleha Akter, Md. Ehsanul Hoque Mazumder, Md. Sohel Rana (Journal of Applied Pharmaceutical Science)
Musa sapientum L. ssp. sylvestris (Family: Musaceae) is a popular edible fruit. It is used by the traditional healers in the treatment of diarrhoea and dysentery. In the present study, methanolic extracts of peel (MSPE), pulp (MSPU) and seed (MSSE) of the fruit were investigated for in vitro antioxidant activity using DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging capacity, reducing power, CUPRAC (Cupric Reducing Antioxidant Capacity) andtotal antioxidant capacity. The phenolic content of the extracts were also determined. The plant extracts showed a direct concentration dependent increase in scavenging DPPH radical. MSSE showed better scavenging activity than MSPE and MSPU with an IC50 value of 54.92 μg/ml, while the standard antioxidant, ascorbic acid, showed an IC50 value of 13.75 μg/ml. The Fe3+/ferricyanide to ferrous and cupric ion reduction capacity of MSSE were better than the reference agent ascorbic acid. All three extracts showed good results in total antioxidant assay. MSSE was also found to contain good amount of phenols (244.38 mg/g of plant extract in GAE). The results of this study indicate that MSSE has strong in vitro antioxidant activity.
Keywords: Musaceae, antioxidant, free radical scavenging, banana.